Exploring the anticancer potential of traditional herbs from Tamil Nadu: a narrative review of ethnomedicinal insights and scientific evidence - Nair, Pradeep M. K.; Pandian, Ayswarya Rohini; Mathapati, Vaishali; B., Shobhitha Tantry; Sai, Abhay; Pai, Navya; Sudarshan, Shanmugam; Mahalingam, Manickam; Silwal, Karishma (Frontiers in Immunology, 2025)
BackgroundIndia, has a rich ethnomedicinal tradition where numerous herbs are used in cancer care. However, scientific validation of these practices remains limited. This narrative review explores the phytochemical mechanisms underlying their anti-cancer effects of 32 herbs identified by herbal activists, including physicians and traditional healers from Tamil Nadu, India, for their purported anticancer properties.MethodsA narrative review was conducted using PubMed, Scopus, and Google Scholar to identify studies published between 2014 and January 2025 on 32 selected anecdotal herbs. Eligible studies included in vitro, in vivo, clinical, and in silico investigations. Data extraction by five independent reviewers focused on botanical and common names, bioactive compounds, mechanisms of anticancer activity, cancer types studied, and evidence level (preclinical vs. clinical).ResultsHerbs such as Withania somnifera, Curcuma longa, and Annona muricata exhibited strong preclinical and limited clinical anticancer activity through apoptosis induction, inhibition of angiogenesis and metastasis, immune modulation, and synergy with standard therapies. Most other herbs remain at the preclinical stage, with minimal clinical data. Only Catharanthus roseus (purified) and Curcuma longa (formulations) have limited clinical application. Challenges including poor bioavailability, lack of standardization, safety concerns, and toxicity (e.g., Annona muricata, Gloriosa superba) hinder clinical translation, underscoring the need for rigorous evaluation.ConclusionTraditional herbs demonstrate notable experimental anticancer potential, yet clinical validation is limited. Integrating ethnomedicinal knowledge with systematic research could guide future cancer therapies and inform policy development in integrative oncology.